Generalized lichenoid drug eruption associated with imatinib mesylate therapy - Sudip Kumar Ghosh (Wolters Kluwer Medknow Publications, 2013)
Imatinib mesylate (IM), an anticancer drug, has been widely used to treat chronic myeloid leukemia (CML), gastrointestinal stromal tumors (GIST), and dermato-fibrosarcoma protuberans. Cutaneous reactions to IM have been reported to occur in varying number of patients in different case series. Non-lichenoid cutaneous reactions secondary to IM have been well-documented in the literature and are the commonest non-hematologic adverse reactions associated with its use. Lichenoid drug eruption (LDE) associated with IM therapy has rarely been reported in the literature. A case of a generalized LDE associated with IM therapy has been described here for its rarity and interesting clinical presentation. As the clinical usage of IM is increasing, one might expect an increasing number of similar patients in the future. It is thus important to realize the potential of IM to produce LDE and to differentiate this entity from idiopathic lichen planus. In the present article, the reports of IM-associated LDE, described in the PubMed and Medline database (in English language literature), have also been reviewed.